Topsoil removal improves various restoration treatments of a Mediterranean steppe (La Crau, southeast France). Issue 2 (14th September 2013) - Jaunatre, Renaud; Buisson, Elise; Dutoit, Thierry; Marrs, Rob
Abstract Question Can topsoil removal improve restoration efficiency of several ecological engineering techniques (nurse species seeding, hay transfer and soil transfer) for restoring a Mediterranean steppe, species‐rich plant community? Location La Crau area, southeast France (Provence). Methods After the rehabilitation of a 357‐ha herbaceous, sheep‐grazed rangeland suitable for threatened steppe birds in a formerly abandoned industrial orchard in the last French Mediterranean steppe (La Crau area), four experimental treatments were applied, with or without topsoil removal. Topsoil was removed on a 5000‐m² area and the four treatments (control, nurse species seeding, hay transfer and soil transfer) were applied within this area where topsoil was removed and within the area where topsoil was not removed. Three years later, soil chemistry, soil seed bank, vegetation cover and height, plant species richness, composition and diversity were compared. Results Removing topsoil partly restored soil conditions and significantly reduced the non‐target seed bank. Moreover, species richness and similarity to the reference steppe was significantly increased with topsoil removal. Topsoil removal, combined with soil transfer and hay transfer, created a community that most closely resembled the reference during the study period. Conclusion In order to restore plant community composition, topsoil removal is a relevant method to increase the efficiency of other ecological restoration techniques, especially those that strengthen dispersal processes.